2015
DOI: 10.2217/imt.15.103
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targets for Natural Killer/T-cell Lymphoma Immunotherapy

Abstract: SummaryExtranodal natural killer/T-cell lymphoma, nasal type (NKTL) is a rare but highly aggressive Epstein-Barr virus-related malignancy, which mainly occurs in nasopharygeal and nasal/paranasal areas. In addition to its high prevalence in Asian, Central American and South American populations, its incidence rate has been gradually increasing in Western countries. The current mainstay of treatment is a combination of multiple chemotherapies and irradiation. Although chemoradiotherapy can cure NKTL, it often c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…The results showed that the expression of ABCC4 in SNK-6/ADM and SNK-6/ADM-SP were both higher than that in SNK-6, while the ABCG2 expression was significantly increased in SNK-6/ADM-SP cells. What was more, we considered that the main factor underlying SNK-6/ADM drug resistance was ABCC4 and ABCG2 rather than P-gp, which is the most classic MDR protein, and consistent with recent studies [ 4 , 25 ] suggesting the absence of absolute correlation between P-gp and chemotherapy resistance. Further results showed that the doxorubicin resistance in SNK-6/ADM-SP cells transfected with shRNAs targeting ABCC4, ABCG2 and ABCC4 + ABCG2 was significantly decreased compared with the sh-control groups, indicating the vital roles of ABCC4 in drug resistance and ABCG2 in conservative characteristics of SNK-6/ADM-SP cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results showed that the expression of ABCC4 in SNK-6/ADM and SNK-6/ADM-SP were both higher than that in SNK-6, while the ABCG2 expression was significantly increased in SNK-6/ADM-SP cells. What was more, we considered that the main factor underlying SNK-6/ADM drug resistance was ABCC4 and ABCG2 rather than P-gp, which is the most classic MDR protein, and consistent with recent studies [ 4 , 25 ] suggesting the absence of absolute correlation between P-gp and chemotherapy resistance. Further results showed that the doxorubicin resistance in SNK-6/ADM-SP cells transfected with shRNAs targeting ABCC4, ABCG2 and ABCC4 + ABCG2 was significantly decreased compared with the sh-control groups, indicating the vital roles of ABCC4 in drug resistance and ABCG2 in conservative characteristics of SNK-6/ADM-SP cells.…”
Section: Discussionsupporting
confidence: 84%
“…Current treatment strategies are not effective and chemoresistance leads to poor prognosis [ 5 , 14 ]. The mechanism of oncogenesis and biological characteristics of ENKL which provide important insights into potential therapeutic options is not clear [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of c-Met or checkpoint blockade with peptide vaccine would be an attracting treatment option in NNKTL. The potential of immunotherapy against NNKTL has been summarized in a review article (112). Because NNKTL is an EBV-related disease, gene therapy to knockout EBV-related proteins or miR would be a fundamental solution to remove NNKTL cells.…”
Section: Establishment Of Novel Treatments For Nnktlmentioning
confidence: 99%
“…In the past 10 years, survival of patients has been improved greatly by antibodies targeting immune checkpoints in a number of human cancers, such as melanoma, renal cancer, colon cancer, and lung cancer. NKTCL might also be targetable for therapeutic antibodies owing to 67% of NKTCL samples expressing PD-L1 [ 17 ]. Lastly, Kwong et al [ 18 ] reported high efficacy of pembrolizumab in relapsed/refractory NKTCL that failed on L-asparaginase.…”
Section: Discussionmentioning
confidence: 99%